Alternatif Desain Pembelajaran pada Masa Adaptasi Kebiasaan Baru (AKB) di Sekolah Dasar - Mutaqin, Ejen Jenal; Asyari, Lutfi; Gunawan, Dani; Nugraha, Widdy Sukma (IPI Press, 2023)
This community service aims to provide insight into knowledge about learning strategies during the AKB period in Elementary School Malangbong Garut District, by providing insight into the importance of solving learning problems related to professional development to increase professionalism for educators during the adaptation of new habits. The problem is resolved in three stages of activities, namely preparation, implementation and evaluation. The results of community service activities show the level of success with an indication of a similar mindset of equivalent educators, a positive response from community service participants related to solving learning problems during the AKB period, and most (75%) participants have understood the concept of developing learning strategies what to do during the Covid-19 pandemic.